The role of preoperative axillary ultrasound and fine-needle aspiration cytology in identifying patients with extensive axillary lymph node involvement. Issue 11 (November 2017) - Maráz, Robert; Zombori, Tamás; Ambrózay, Éva; Cserni, Gábor
Abstract: Introduction: In the recent past, both clinically node-positive and node-negative but sentinel node-positive patients underwent axillary lymph node dissection (ALND), although the two groups seem to have substantially different degree of nodal involvement. Methods: Data on consecutive primary breast cancer patients with documented axillary ultrasound (AXUS) results who underwent ALND between January 2003 and December 2015 either because of AXUS-guided fine needle aspiration (A-FNAC) results or because of a positive sentinel lymph node were retrospectively analysed. Results: After exclusions, 316 patients staged by SNB and ALND with negative AXUS or A-FNAC (group A) were compared with 159 patients having positive A-FNAC results (group B). Tumour size and the proportion of mastectomies were greater, histological grade higher and lymphovascular invasion more frequent in Group B, where palpable lymph nodes were also more common. The proportion of cases with extensive nodal involvement (pN2 and pN3 cases) was about 3 times as much in Group B (63%) than in Group A (18%). Removal of the 50 patients with palpable lymph nodes from the analysis did not greatly influence these proportions: 60% and 19% extensive nodal involvements were noted, respectively. In this series, patients with suspicious AXUS and negative A-FNAC had more often extensive nodal involvement (25%) than AXUS negative patients (17%). Conclusions: Patients in whom axillary metastases are detected by ultrasound-guided biopsy have significantly more involved nodes than SLNB-positive patients, and therefore are likely to benefit from axillary treatment.